Effect of Parent‐Based Sexual Health Education on Parent–Adolescent Communication and Adolescent Sexual Behavior: A Systematic Review and Meta‐Analysis. - Gutu, Birhanu; Mahimbo, Abela; Percival, Nikki; Demant, Daniel (Perspectives on Sexual & Reproductive Health, 2025)
Background: Parent‐based sexual education interventions have a positive impact on adolescent sexual and reproductive health. However, despite these positive outcomes, there is a lack of comprehensive research to understand the effectiveness of these programs across different communities and demographics. Methods: We conducted a systematic search of databases from January 2013 to April 2023 and identified 51 published studies conducted globally on the effects of parent‐based sexual education. We conducted meta‐analyses to understand the pooled effect of interventions on parent–adolescent communication outcomes and adolescent sexual and reproductive behaviors. Results: This review includes 51 studies. Most of the included studies (n = 36, 68.6%) were conducted in high‐income countries; 17 (33.3%) involved only mothers, and 37 (72.5%) stated they were based on theoretical frameworks. The systematic review showed that interventions on sexual communication had mixed effects on parent and adolescent‐related outcomes. The meta‐analysis, however, showed positive effects on parent‐reported sexual health communication frequency, adolescent‐reported sexual health communication frequency, parental attitude, and parental self‐efficacy, Cohen's d = 0.32, 0.26, 0.38, and 0.41, respectively. Conclusion: Parent‐based sexual health education interventions positively impact various aspects of parent–adolescent sexual health communication and behavior, suggesting the effectiveness of the intervention in different social, cultural, and economic contexts. The lack of research in low‐ and middle‐income nations and limited paternal participation highlights the need for further research.